PROFESSIONAL-PEDAGOGICAL COMPETENCE OF THE TEACHER AND ITS ROLE IN SOCIETY - Sattorov Eldor Bobir o‘g‘li (Western European Studies, 2023)
This article provides feedback on the professional skills of the teacher, level of competence, communicative abilities, the images of a progressive, creative and innovative teacher and the educational views of our great thinkers, the position of the teacher in society.
Keywords: educational; creative; professional; competence